Application of conjugable oxidation products assay in assessment of gamma-irradiated palm olein - Woodward, T.W. (2023)
Samples of palm olein were irradiated with y-rays up to 12kGy. The extent of peroxidition in irradiated samples was determined by conjugable oxidation products (COP) assay and the result were compared with the UV absorbance at 232 nm. The two parameters were poorly correlated (r = 0.6321) within the range of doses used. The effect of y-irradiation is mainly to oxidise linoleic acid (Cl8:2) as this component is the major di unsaturated fatty acid in palm oil.